Dinamika Perkembangan Islam Di Asia Tenggara Perspektif Histori - M Dahlan M (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
This writing discusses about Islamic development  in south East Asia. It used library methode aplying qualitative analysis. The data of this writing was arranged based on heuristic analysis, critics, and interpretation. The writer concludes that Islam has developed since 9th century to the present. Islamic development stage can be divided into three era; pra colonial, colonial era, and pasca colonial. Islamic development in south Asia was more dominantly influenced by its supporting aspects bringing the islamic community persistenly live and has coloured the historical pieces in this area.